2021
DOI: 10.3390/en14217336
|View full text |Cite
|
Sign up to set email alerts
|

Development of Stable Mixed Microbiota for High Yield Power to Methane Conversion

Abstract: The performance of a mixed microbial community was tested in lab-scale power-to-methane reactors at 55 °C. The main aim was to uncover the responses of the community to starvation and stoichiometric H2/CO2 supply as the sole substrate. Fed-batch reactors were inoculated with the fermentation effluent of a thermophilic biogas plant. Various volumes of pure H2/CO2 gas mixtures were injected into the headspace daily and the process parameters were followed. Gas volumes and composition were measured by gas-chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Since flow-through reactors are optimized to maximum H 2 conversion efficiency, generally low hydrogen injection rates are applied that limit methane production rates. In spite of the intermittent operation of the fed-batch reactor, a remarkable 1000 mL L −1 d −1 H 2 consumption rate was attained, while methane was enriched up to 95% [86].…”
Section: Bioreactor Design and Operationmentioning
confidence: 99%
“…Since flow-through reactors are optimized to maximum H 2 conversion efficiency, generally low hydrogen injection rates are applied that limit methane production rates. In spite of the intermittent operation of the fed-batch reactor, a remarkable 1000 mL L −1 d −1 H 2 consumption rate was attained, while methane was enriched up to 95% [86].…”
Section: Bioreactor Design and Operationmentioning
confidence: 99%
“…The key methanogens involved depend on how the P2M process is achieved, i.e., mixed anaerobic communities are required for in-situ P2M. At the same time, pure cultures are essential for ex-situ P2M, which could be enriched from full-scale anaerobic digestion plants [246,247]. Further, the converted methane from H2 could be either utilized directly to replace natural gas or converted back to hydrogen.…”
Section: Recent Advances and Future Research Directionsmentioning
confidence: 99%
“…Another study found that psychrophilic conditions can inhibit methanogenic activity but either mesophilic or psychrophilic conditions can enrich homoacetogens [ 45 ]. To better understand the microbial communities and their functioning, omics techniques such as metagenomics and metatranscriptomics have been exploited to unravel in more detail the community members and their metabolic functions during biomethanation of hydrogen [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%